Megafauna and ecosystem function from the Pleistocene to the Anthropocene - Malhi, Yadvinder; Doughty, Christopher E.; Galetti, Mauro [UNESP]; Smith, Felisa A.; Svenning, Jens-Christian; Terborgh, John W. (Natl Acad Sciences, 2016)
Large herbivores and carnivores (the megafauna) have been in a state of decline and extinction since the Late Pleistocene, both on land and more recently in the oceans. Much has been written on the timing and causes of these declines, but only recently has scientific attention focused on the consequences of these declines for ecosystem function. Here, we review progress in our understanding of how megafauna affect ecosystem physical and trophic structure, species composition, biogeochemistry, and climate, drawing on special features of PNAS and Ecography that have been published as a result of an international workshop on this topic held in Oxford in 2014. Insights emerging from this work have consequences for our understanding of changes in biosphere function since the Late Pleistocene and of the functioning of contemporary ecosystems, as well as offering a rationale and framework for scientifically informed restoration of megafaunal function where possible and appropriate.
Keywords: extinctions; trophic cascades; vegetation structure; biogeochemistry; rewilding